Estudo termodinâmico e avaliação experimental do protótipo 01 do sistema de refrigeração por absorção com o par água-brometo de lítio da Recogás. - Cordeiro, Marcos Cézar Lima (2012)
The present study describes a theoretical and experimental analysis of the Prototype 01, this being an absorption refrigeration machine of simple effect with the pair water-lithium bromide as a working fluid and uses natural gas as an energy source for the steam generator, aiming the simulation of waste heat cogeneration. The unit has been developed and constantly improved in Rede Cooperativa de Pesquisa Norte/Nordeste do Gás Natural RECOGÁS-N/NE building present in Instituto de Energia Sustentável (IES) at the Universidade Federal da Paraíba. This unit has a carbon steel frame, using a stainless steel pipe. One goal of the study is an approximation of the results obtained experimentally in this study with the theoretical results for SANTOS (2005). In order to purpose validation was used Engineering Equation Solver (EES) software to obtain the properties, especially those inherent to the working fluid, using input data obtained experimentally. Still aims to expose inherent and unique aspects of an essentially experimental work, which will be addressed experimental methodology applied by the use of the materials used, the discussions regarding aspects of construction and operation of the unit, problems identified, interventions in the pilot plant and finally proposing solutions to some of the observed problems.